A striking sexually dimorphic new species of Castolus (Hemiptera: Heteroptera: Reduviidae) from Colombia, with new records from Neotropical countries and taxonomic notes on the genus - Forero, Dimitri; Mejía-Soto, Andrés (Zootaxa, 2021)
The New World genus Castolus Stål, 1858 (Hemiptera: Heteroptera: Reduviidae) contains 16 described species. Based on material from northern Colombia we describe Castolus rafaeli sp. nov., and key all known species. The following new synonyms are proposed: Castolus nigriventris Breddin, 1904 = C. bicolor Maldonado, 1976, syn. nov.; and C. subinermis (Stål, 1862) = C. annulatus Maldonado & Brailovsky, 1992, syn. nov. = Mucrolicter alienus Elkins, 1962, syn. nov. Because M. alienus is the type species of the currently monotypic genus Mucrolicter Elkins, 1962, the proposed synonymy results in the following generic synonym: Castolus Stål, 1858 = Mucrolicter Elkins, 1962, syn. nov. New country records are provided for two species: Castolus plagiaticollis Stål, 1858 is recorded new for Colombia; and Castolus rufomarginatus Champion, 1899 for Costa Rica, Colombia, and Ecuador. Additional localities are provided for species from Colombia and other Neotropical countries based on both specimens from entomological collections and observations from the citizen science initiative iNaturalist.